AN ANALYSIS OF THE TRANSLATION OF SIMILES AND METAPHORS IN THE GHOST, A NOVEL WRITTEN BY DANIELLE STEEL - Rina Nurmala Dewi, - (2010)
The research entitled "An Analysis of the Translation of Similes and Metaphors in The Ghost, A Novel Written by Danielle Steel" is aimed at finding out the types of similes and metaphors found in The Ghost and the strategies used by the translator in translating them. Descriptive qualitative method is applied in conducting the research. The English similes found are classified based on Keraf's classification while the metaphors are classified based on Larson's. And then the translations are analyzed based on translation procedure proposed by Newmark. According to this research, it can be concluded that closed simile, open simile, dead metaphor and live metaphor are found in the novel, in which open similes are the most common figures of comparison used by the author in delivering the messages or about 42.03% of figurative of comparison belong to open simile. While of the translation procedure, reduction procedure is mostly used by the translator in translating those similes and metaphors since the percentage is 20.29%. One of the reasons why reduction procedure is mostly used is because not all similes and metaphors are understood in the target language. As long as the similes and metaphors are not important enough in the text and the translation does not change the meaning of the text reduction procedure can be applied. Keywords: Translation, simile, metaphor